Thinking green building smart - Claudin, Craig; Mohl, Steve; Shopware (Firm). (Hamilton, NJ : Shopware, 2010)
Explores the thought process at the core of green architectural design and construction as it takes viewers behind the scenes of an architectural firm specializing in sustainable design, a remodeler who has built a green construction business, a supplier of eco-friendly building materials, and a homeowner who has remodeled his house from the ground up using green materials, technologies, and practices.
Director of photography, Craig Claudin ; editors, Craig Claudin, Steve Mohl.
Host: Robert Post.
Keywords: Sustainable buildings -- Design and construction; Sustainable architecture; Architecture and energy conservation